Testicular pathological alterations associated with SARS-CoV-2 infection - Ly, Judy; Campos, Rafael K.; Hager-Soto, E. Eldridge; Camargos, Vidyleison N.; Rossi, Shannan L. (Frontiers in Reproductive Health, 2023)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is the etiologic agent of the coronavirus disease 2019 (COVID-19), which caused one of the pandemics with the highest mortalities with millions of deaths and hundreds of millions of cases to date. Due to its potential for airborne transmission, many studies have focused on SARS-CoV-2 primarily as a respiratory disease. However, the spread of SARS-CoV-2 to non-respiratory organs has been experimentally demonstrated and clinically observed. During autopsy studies, histopathological lesions, and disruption of the blood-testes barrier (BTB) have been observed in the male reproductive tract. Here, we review findings from both autopsy cases and animal models that demonstrate testicular disease due to COVID-19 and present an overview of the pathological alterations that occur in the testes resulting from SARS-CoV-2 infection and explore its potential mechanisms.